Acquisition Data System Through the Internet Networking Case Study Room With Temperature Measurement Sensor DS1621 - INDRIANTO INDRIANTO INDRIANTO (Majalah SIKOMTEK, 2006)
Sensor in industrial and other much needed because with the sensor adannya industrial areascan be easily able to control equipment remotely. The sensor can be used if there is a series ofADC and DAC, and required a calibration for the sensor can measure an exact quantity. Byusing DS1621 sensors then it is not necessary because the DS1621 is a sensor that 'smart'(Intelegent Sensor). DS1621 does not require the microcontroller and does not requirecalibration.Temperature Measuring Equipment Design Room With DS1621 Sensor Networks ThroughInternet-Based Personal is a tool for censorship that uses DS1621 temperature. Data sent bythe temperature sensor can be retrieved through the Internet network so that this equipmentcan be accessed from anywhere as long as it is connected with the Internet. This circuit has atemperature of -20 C. .......+ 125 Software used to display the results of temperaturemeasurement is HTML. Use the Windows 2000 server as a server on this design is veryhelpful. Because it makes nearly all computer activity becomes easier, faster and fullyintegrate with the Internet because there are DNS (Domain Name System) and IIS (InternetInformation Service).